MANAJEMEN INOVASI PEMBELAJARAN BERBASIS E-LEARNING DAN BLENDED LEARNING, SYSTEMATIC LITERATURE REVIEW - Puput Puspito Rini (STAI Darul Qalam Tangerang, 2024)
The management of e-learning-based learning innovation and blended learning is rapidly growing in global higher education, transforming the way institutions design and manage learning experiences through flexible and sustainable digital technology integration. This research aims to comprehensively examine the management of e-learning-based learning innovations and blended learning in higher education, including pedagogical innovations, student motivation factors, institutional implementation strategies, and digital technology mapping as the foundation of inclusive and sustainable learning policies. The method used is Systematic Literature Review (SLR)